Beyond Research Ethics: Dialogues in Neuro-ICT Research - Stahl, Bernd Carsten; Akintoye, Simisola; Fothergill, B. Tyr; Guerrero, Manuel; Knight, Will; Ulnicane, Inga (Frontiers in Human Neuroscience, 2019)
The increasing use of information and communication technologies (ICT) to help facilitate neuroscience adds a new level of complexity to the question of how ethical issues of such research can be identified and addressed. Current research ethics practice, based on ethics reviews by institutional review boards (IRB) and underpinned by ethical principalism, has been widely criticised and even called ‘imperialist’. In this paper, we develop an alternative way of approaching ethics in neuro-ICT research, based on discourse ethics, which implements responsible research and innovation through dialogues. We draw on our work in Ethics Support, using the Human Brain Project as empirical evidence of the viability of this approach.